Morphology-dependent catalysis by Co3O4 nanostructures in atmospheric pressure carbon dioxide hydrogenation - Gupta, Sharad; Jain, Preeti; Jagadeesan, Dinesh; Vinod, C. P. (Journal of Physical Chemistry C, 2023)
In this work, three Co3O4 nanostructureswith different morphologies (cubes, rods, and sheets) were synthesizedusing a hydrothermal method and tested for the CO2 hydrogenationreaction. The physicochemical properties of the structured Co3O4 were well characterized by X-ray diffraction(XRD), Raman spectroscopy, field-emission scanning electron microscopy(FESEM), transmission electron microscopy (TEM), high-resolution transmissionelectron microscopy (HRTEM), hydrogen temperature-programmed reduction(H-2-TPR), and X-ray photoelectron spectroscopy (XPS) techniques.Based on the characterization, cube, rod, and sheet Co3O4 nanostructures were found to expose the (100), (110),and (112) planes, respectively. The effect of cobalt oxide morphologieswith different exposed surfaces on the activity and selectivity towardCO(2) hydrogenation reaction in a plug-flow reactor operatedbetween 200 and 400 & DEG;C under atmospheric pressure conditionswas explored. The results establish a correlation of the catalyticactivity with morphological structures in the order rods > sheets> cubes. H-2-TPR and XPS studies demonstrated that thehighreducibility of Co3O4 rod makes it an excellentcatalyst for CO2 hydrogenation.